Analisis Risiko Keterlambatan Pada Proyek Pembangunan Gedung Rusun 3 Lantai Kogabwilhan II - Tobing, Valentino Gracia Lumban; Purwantoro, Almuntofa (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2026)
reduced work quality. Previous studies have generally been descriptive and have not quantitatively and comprehensively modeled duration uncertainty. This study aims to analyze delay risk by evaluating the probability of project completion and identifying the activities that most significantly influence delays. The case study was conducted on the construction project of the TNI Kogabwilhan II Flats in Balikpapan. The methods used include the Critical Path Method (CPM) to determine the critical path, Earned Value Management (EVM) to estimate the remaining duration based on actual progress, and Monte Carlo simulation to obtain the probability distribution of project duration. Sensitivity analysis is used to identify dominant activities and formulate appropriate mitigation strategies. The results show that the number of critical activities decreased from 67 to 37, with an estimated remaining project duration of 198 days. Under the highest deviation scenario, the P50 duration is 199.206 days and the P90 duration is 201.245 days. Roof slab work is identified as the most influential factor, while fast tracking is effective for non-structural activities such as practical columns.